2021
DOI: 10.1136/bjophthalmol-2021-319431
|View full text |Cite
|
Sign up to set email alerts
|

Normative data and percentile curves for axial length and axial length/corneal curvature in Chinese children and adolescents aged 4–18 years

Abstract: PurposeTo develop age-specific and gender-specific reference percentile charts for axial length (AL) and AL/corneal radius of curvature (AL/CR) and, to use percentiles to determine probability of myopia and estimate refractive error (RE).MethodsAnalysis of AL, cycloplegic RE and CR of 14 127 Chinese participants aged 4–18 years from 3 studies. AL and AL/CR percentiles estimated using Lambda-Mu-Sigma method and compared for agreement using intraclass correlation (ICC). Logistic regression was used to model risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
42
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 33 publications
10
42
2
Order By: Relevance
“…However, we found that in patients with cbEGF-like mutations, the total corneal K1 increased with aging (r s = 0.294, p = 0.038). This differs from the overall findings for MFS patients with lens subluxation ( Chen et al, 2018a ) or healthy children ( He et al, 2021 ; Liu et al, 2021 ), indicating the specific role of cbEGF-like mutations, rather than general FBN1 mutations, in age-related corneal changes.…”
Section: Discussioncontrasting
confidence: 86%
“…However, we found that in patients with cbEGF-like mutations, the total corneal K1 increased with aging (r s = 0.294, p = 0.038). This differs from the overall findings for MFS patients with lens subluxation ( Chen et al, 2018a ) or healthy children ( He et al, 2021 ; Liu et al, 2021 ), indicating the specific role of cbEGF-like mutations, rather than general FBN1 mutations, in age-related corneal changes.…”
Section: Discussioncontrasting
confidence: 86%
“…Emmetropia is a balance between AL, corneal power and lens power (40). That means longer eyes can be compensated by less lens power or flatter corneas to keep emmetropic (41)(42)(43)(44)(45). So future studies should take lens power and corneal radius of curvature into consideration to account for their possible compensation of greater axial growth.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, cycloplegic assessment of SE is not always practical for regular eye examinations and myopia screenings. Previous studies have confirmed that axial length (AL) elongation is correlated with myopia progression 9–11 . Moreover, the measurement of AL is fast, noninvasive and accurate with variability limited to a few microns between biometry instruments, whereas the repeatability of refractive error measurements between autorefractors is around ±0.50 D 11,12 .…”
Section: Introductionmentioning
confidence: 91%
“…Previous studies have confirmed that axial length (AL) elongation is correlated with myopia progression. [9][10][11] Moreover, the measurement of AL is fast, noninvasive and accurate with variability limited to a few microns between biometry instruments, whereas the repeatability of refractive error measurements between autorefractors is around ±0.50 D. 11,12 In addition, myopia in children and adolescents is primarily caused by excessive axial elongation, defined as axial myopia, 13 and this excessive AL growth is directly related to the risk of complications in the posterior pole. 14,15 Therefore, the measurement of AL is fundamental in myopia management and treatment, and AL elongation could be a potential indicator for SE progression.…”
Section: O R I G I N a L A R T I C L E Association Between Axial Leng...mentioning
confidence: 99%